Upon a slight rearrangement this problem gets a lot simpler to see.
x^3-x+2x^2-2=0 now factor 1st and 2nd pair of terms...
x(x^2-1)+2(x^2-1)=0
(x+2)(x^2-1)=0 now the second factor is a "difference of square" of the form:
(a^2-b^2) which always factors to (a+b)(a-b), in this case:
(x+2)(x+1)(x-1)=0
So g(x) has three real zero when x={-2, -1, 1}
Answer:
Step-by-step explanation:
The chance os 50%
Answer:
2/3&1/6
2/3- 1/6
the LCM for 3 and 6 is 6
=(2x6)/(3x6) -(1x6)/(6x6)
=4/6-1/6
=(4-1)/6
find the difference
= 3/6
=1/2
2/3-1/6= 1/2
By using LCM method, 1/2 is the equivalent fraction by subtracting 1/6 from 2/3.
2/3&1/6
2/3- 1/6
cross multiply
2x6-1x3/3x6
simplify
12-3/18
=9/18
= 1/2
2/3-1/6 = 1/2
By using cross multiplication method, 1/2 is the difference between two fractions 2/3 and 1/6.
Step-by-step explanation:
hope that helps>3